Dystocia Due to Hydrocephalus Monster in A Murrah Buffalo - Dalal, Jasmer; Singh, Gyan (The Indian Journal of Animal Reproduction, 2023)
The present communication describes successful management of an unusual case of dystocia due to hydrocephalus monster with bilateral anophthalmia conditionin 7-year-old Murrah buffalo.
Keywords: Buffalo; dystocia; Hydrocephalus; monster